Spatiotemporal Patterns of Water Stable Isotope Compositions at the Shale Hills Critical Zone Observatory: Linkages to Subsurface Hydrologic Processes. Issue 4 (2nd August 2013) - Thomas, Evan M.; Lin, Henry; Duffy, Christopher J.; Sullivan, Pamela L.; Holmes, George H.; Brantley, Susan L.; Jin, Lixin
Abstract : To better understand flow pathways and patterns in the subsurface, a stable isotope monitoring network was established at the Susquehanna‐Shale Hills Critical Zone Observatory (SSHCZO). Soil water samples were collected approximately biweekly using suction‐cup lysimeters installed at multiple depths along four different transects in the catchment. Groundwater and stream water were collected daily in the valley using automatic samplers, while precipitation samples were collected automatically on an event basis. The 3+ years (2008–2012) of monitoring data showed strong seasonal precipitation isotope compositions, which were imprinted in seasonal patterns of soil water at different spatial locations and depths. The groundwater isotope composition remained relatively constant throughout the year and closely matched the yearly amount‐weighted precipitation average, suggesting groundwater received recharge water in each season, although recharge mechanisms differed between growing and nongrowing seasons. Soil water samples showed clear attenuation with depth, with the largest variability in the shallow soil water (≤30 cm) mirroring precipitation inputs, moderate variability in the intermediate depths (40–100 cm), and the least variability in the deep soil water (≥120 cm) where the average remained near the groundwater average. Soil water isotope composition profiles also provided clear evidence for preferential flow occurring both laterally and vertically in different seasons and at various soil depths in the catchment. Putting all together, the extensive dataset of soil water isotopic compositions obtained in this study have provided a number of insights into complex subsurface hydrologic processes that are transferable to other similar landscapes.